To identify the solution for the system of equations given by the two lines, we should find the point where the two equations intersect.
From the table provided, we can deduce the y-values corresponding to different x-values for both equations:
For \( y = 2x - 5 \):
- \( x = 0 \): \( y = -5 \)
- \( x = 1 \): \( y = -3 \)
- \( x = 2 \): \( y = -1 \)
- \( x = 3 \): \( y = 1 \)
For \( y = x - 3 \):
- \( x = 0 \): \( y = -3 \)
- \( x = 1 \): \( y = -2 \)
- \( x = 2 \): \( y = -1 \)
- \( x = 3 \): \( y = 0 \)
Now, letβs find the common (x, y) values in both equations:
For \( x = 2 \):
- The y-value for \( y = 2x - 5 \) is \( -1 \).
- The y-value for \( y = x - 3 \) is also \( -1 \).
Since both equations give the same output when \( x = 2 \), the point (2, -1) is a solution to the system of equations.
Thus, the answer is:
\( (2, -1) \)